Market power and welfare in asymmetric divisible good auctions - Carolina Manzano Tovar; Xavier Vives (Theoretical Economics, 2021)
We analyze a divisible good uniform-price auction that features two groups, each with a finite number of identical bidders, who compete in demand schedules. In the linear-quadratic-normal framework, this paper presents conditions under which the unique equilibrium in linear demands exists and derives novel comparative statics results that highlight the interaction between payoff and information parameters with asymmetric groups. We find that the strategic complementarity in the slopes of traders' demands is reinforced by inference effects from prices, and we display the role of payoff and information asymmetries in explaining deadweight losses. Furthermore, price impact and the deadweight loss need not move together, and market integration may reduce welfare. The results are consistent with the available empirical evidence.
Keywords: D44; D82; G14; E58; 330; Demand/supply schedule competition; private information; liquidity auctions; treasury auctions; electricity auctions; market integration